Criteria for the diagnosis of diffuse uterine myohypertrophy - Traiman, Paulo [UNESP]; Saldiva, P.; Haiashi, A.; Franco, M. (Elsevier B.V., 1996)
Objectives: Diffuse uterine myohypertrophy (DUMH) is a condition clinically diagnosed by the presence of uterine bleeding, homogeneous and diffuse uterine enlargement, and absence of any myoendometrial cause of bleeding. Since the morphologic criteria for the diagnosis of this entity are still controversial, this study aimed to investigate the clinical presentation and the morphologic findings of the cases of DUMH presenting at the University Hospital of Botucatu, São Paulo, Brazil, Methods: We retrospectively studied 43 consecutive patients with DUMH submitted to hysterectomy (test group) and compared the findings with those obtained from 28 patients submitted to hysterectomy due to a prolapsed uterus (control group). There were no significant differences in age, weight or height between the two groups. Results: the uterine weight of the DUMH group (mean +/- S.D. 157.4 +/- 46.4 g) was significantly heavier than that of the control group (99.5 +/- 35.4 g) and myometrial thickness was significantly greater in the DUMH group (2.5 +/- 0.5 cm) than in the control group (1.9 +/- 0.4 cm). No positive correlation was observed between increased uterine weight and parity, but there was a positive correlation between uterine weight and myometrial thickness. on the basis of the present study, we suggest that the diagnosis of DUMH be made clinically and in cases of uterine weight greater than or equal to 120 g and myometrial thickness greater than or equal to 2.0 cm. In addition, 10 cases of each group were analyzed by morphometry to evaluate interstitial fibrosis and myometrial hypertrophy. The data showed that the increase in uterine weight in DUMH is caused by enlargement of individual myometrial fibers rather than accumulation of interstitial collagen. Conclusion: Discriminant analysis to estimate the diagnostic significance of a number of clinical and pathologic variables (age, parity, uterine weight and morphometric parameters) was able to differentiate cases of DUMH from controls in 100% of the patients.
Keywords: diffuse uterine myohypertrophy; uterus